Isolation and identification of different amino acids and other phytoconstituents through LCMS, GCMS analysis of Ananas comosus and evaluation of antifungal activity - Sipra Sarkar Banerjee,; Dhrubo Jyoti Sen,; Sudip Kumar Mondal,; Sumit Mallick,; Tanmoy Maity,; Arkadeep Mukherjee,; Beduin Mahanty, (The Bioscan, 2025)
4im-The project investigates the presence of different phytoconstituents and antifungal activfiies of protein concentrated part of Pineapple, scientifically known as .4nanas comoSus. Objectis'e-Pineapple scientifically known as Ananas comosus Lnving different phyocoastituents unexplored and evaluation of antifungal activity have to be eatabliahed. Material and method-The pineapple juice have been extracted and lyophihzeA Then ion exchange chromatography was performed to isolate different amino acid. Different salts were used for protein precipita0om and various solvents were used. including petroleum ether, n-hexme, ethanol, methanol, and aqueous media. Then this protein concentrated part wm sent to TAAB Biostudj' center, Koi aqueous extract was send to HB Kolkata for LC IS, n-hexane part was sent to GCMS to IICB, Kokata, The antifungal actin ity was performed with A. niger & C.a1bicans with ethanolis extract and two differcut protein concentration with Sahogaurd media. Results-The amino acids glycine, alanine, phenylalanine, glutainic acid, histidine and argmne were found in isolated part of protein concentratim The LCMS study of aq extract of shnws the presence of Gallic acid, Pyrocatechol, Hydroxytyrosol, Chlorogmic acid, Caffeic acid. Syrineic acid etc. The GCMS atudy ahows the presence of desane, 3,7 -dimethyl-: benzene, 1,3bis(1,1-dimetby1ethyl)-. dodecane, 4-methyl-. dodecane, 2.6.11-trimethyl-; heptadecane. 2.11-2,6,10-himethy1tridecane: nonadecane etc. The antifiingal actix'ity was established for A. niger & C.albicans shh ethanolis enlracl with etbmolic extract and protein concentrated part I.